Piecewise algebraic curves and four-color theorem - Gong, Dian-Xuan; Wang, Ren-Honga (Utilitas Mathematica, 2010)
Using the property of S10-spline, we propose a new approach to study the four-color theorem. In this paper, we study the relationship between piecewise algebraic curves and the four-color theorem, and give a new equivalent condition under the point of piecewise algebraic curve with a matrix interpretation.